The invasive assessment of coronary atherosclerosis and stents using optical coherence tomography: a clinical update. Issue 1 (26th July 2013) - Asrar ul Haq, Muhammad; Layland, Jamie; Mutha, Vivek; Barlis, Peter
Abstract : Ischaemic heart disease (IHD) remains one of the leading causes of death. Atherosclerosis has been intensely researched given the IHD prevalence and the financial impacts on healthcare systems. More recently, in vivo characterisation of coronary atherosclerotic plaque and tissue responses following stent implantation in a coronary artery has been made possible by a novel technology called optical coherence tomography (OCT). OCT is a light-based, invasive, intracoronary imaging modality long applied to the field of ophthalmology and now in clinical use worldwide. It gives a unique view of within the coronary artery using near-infrared light with a resolution of 15 microns, 10 times higher than other invasive coronary imaging techniques like intravascular ultrasound. The technology is being adopted to comprehensively detect features that make plaques 'vulnerable' (eg, large lipid pool, thin, fibrous-cap atheroma), whether stents are implanted optimally within the artery, and visualise the small layers of tissue that form over stent metal surfaces over time, which in turn may provide surrogate markers for long-term stent safety and help guide the optimal duration of dual antiplatelet therapy, a topic of big discussion at the current point of time.